Cyber Borderlines: Exploring the Interplay Between E-Commerce and International Trade Law - Rashaun Prasad (Studies in Law and Justice, 2023)
This review delves into the intricate interplay between e-commerce and international trade law, shedding light on the dynamic challenges and opportunities presented by the digital age. As e-commerce transcends traditional geographical boundaries, it reshapes global trade dynamics, necessitating a reevaluation of existing regulatory frameworks. The paper navigates through the complexities of jurisdiction, data privacy, intellectual property rights, and trade facilitation in the digital era. It critically examines the role of e-commerce platforms and explores the potential for harmonizing international trade rules. By exploring these dimensions, this review contributes to the understanding of how e-commerce intersects with international trade law and the implications for shaping the future of global commerce.